Draft Eighth Five-Year Plan 1990-95 A Summary State Planning Commission Tamil Nadu - Planning Commission (Planning Commission, 1990)
A brief review of the development experience of the State during the planning era, covering a span of about forty years, may provide the back drop against which it will be appropriate, to formulate the Eighth Five-Year Plan. An appraisal of the development experience during this period shows that the State has recorded impressive achievements under several development heads but depressing overall results in certain vital respects. A quick review of the resource endowment position may be the right point to start this appraisal. The State is poorly endowed in respect of natural resources. It is part of the low to moderate rainfall zone and the rainfall is often undependable. Nearly 56 per cent of the area under cultivation depends on this kind of inadequate and unreliable rainfall. The land-man ratio in the State is also quite adverse. Within these constraints, more than 60 per cent of the labour force of the State had all along been engaged in agricultural activities. The State has 7 per cent of the country’s population with 4 per cent of the land area and 3 per cent of the Water resources.
A Summary
Government of Tamil Nadu